Translation-Poems: Blurred Genres and Shifting Authorship in Contemporary English Verse - Jerzy Jarniewicz (Anglica. An International Journal of English Studies)
One of the most interesting tendencies in contemporary English poetry which arguably will develop further and mark the next decades of writing in England, are works which I would call translation-poems, i.e. texts which problematize the distinction between translations and original works, as well as between authors and translators. One could mention here such books as Jo Shapcott’s Tender Taxes (versions of Rilke’s poems), Alice Oswald’s Memorial (a translation of Homer’s The Iliad), and Lavinia Greenlaw’s A Double Sorrow: Troilus and Criseyde (a version of Chaucer’s poem). All three books have been advertised as authored by these English poets; it is only their names that appear on book covers. Significantly, this type of translating, or adapting poetry comes now largely from women writers. Trying to define the blurred genre they are working in, they call it variously: versions, excavations, extrapolations, remixes, etc.